2017
DOI: 10.1097/md.0000000000007739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid–base balance on postoperative course in children with hypoplastic left heart syndrome after the modified Norwood procedure

Abstract: Hypoplastic left heart syndrome (HLHS) is a congenital heart defect that requires 3-stage cardiac surgical treatment and multidirectional specialist care. The condition of newborns in the first postoperative days following the modified Norwood procedure is characterized by considerable hemodynamic instability that may result in a sudden cardiac arrest. It is believed that the most important cause of hemodynamic instability is the fluctuations in redistribution between pulmonary and systemic blood flow.The pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…[28][29][30][31][32][33] Laboratory markers of poor outcomes other than arrest included serum lactate, acid-base balance, central venous oxygen saturation, arterial pH, base excess, and oxygen extraction ratio. [34][35][36][37][38] Two studies identified novel laboratory markers associated with adverse outcomes related to low cardiac output following surgery: alkaline phosphatase and neutrophil gelatinase-associated lipocalin. Further research examining the utility of these novel biomarkers as predictive indices for cardiac arrest, considering its relationship to low cardiac output syndrome, should be explored.…”
Section: Commentsmentioning
confidence: 99%
“…[28][29][30][31][32][33] Laboratory markers of poor outcomes other than arrest included serum lactate, acid-base balance, central venous oxygen saturation, arterial pH, base excess, and oxygen extraction ratio. [34][35][36][37][38] Two studies identified novel laboratory markers associated with adverse outcomes related to low cardiac output following surgery: alkaline phosphatase and neutrophil gelatinase-associated lipocalin. Further research examining the utility of these novel biomarkers as predictive indices for cardiac arrest, considering its relationship to low cardiac output syndrome, should be explored.…”
Section: Commentsmentioning
confidence: 99%
“…9 The assessment of cardiovascular disease prognosis and procedural outcomes highlighted several parameters and biomarkers. [10][11][12][13][14][15] Many of them, including interleukins, microribonucleic acids (microRNAs), tumor necrosis factor alpha (TNF-α), and platelet-leukocyte aggregates, 16,17 have high prognostic value. However, using such markers in clinical practice is not possible, as a profound analysis of inflammatory phenomena is challenging and not costeffective.…”
Section: Introductionmentioning
confidence: 99%